Chronic subdural haematomas in elderly population. Neurosurgical aspects and focus on the single-burr hole technique performed under assisted local anaesthesia. (4th March 2017) - Seizeur, Romuald; Abed-Rabbo, Francis; Obaid, Sami; Saliou, Philippe; Simon, Alexandre; Dam Hieu, Phong; Magro, Elsa
Abstract: Objective: Chronic subdural haematomas (CSDH) is a common pathology that usually affects the elderly population. The incidence of CSDH has recently been increasing with the expansion of the aging population. The objective of our study was to evaluate the outcome following surgical drainage of CSDH in elderly patients. Materials and methods: We performed a retrospective analysis of 455 consecutive patients with CSDHs over a 5-year period. Among them, all 121 patients older than 80-year old were included in the study. Clinical status, comorbidities, type of surgical technique and outcome were analyzed. Outcome at last follow-up was measured using the Markwalder grading score and the Glasgow outcome scale. Results: Patients ranged from 80- to 94-year old with a median age of 84 years (range 80–94). Ninety-eight percent of patients were surgically treated by a small burr hole under assisted local anaesthesia. About 69.2% of patients improved post-operatively. The mortality rate was 6.8%. Conclusion: CSDH is a common pathology in the elderly population. Patients with CSDHs often have comorbodities that need to be considered in deciding whether surgical treatment is indicated. When surgery is elected, small craniostomy techniques performed under assisted local anesthesia is safe and should be favored in this frail population.